2013
DOI: 10.12799/jkachn.2013.24.3.346
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Exercise Program using a Resident Volunteer as a Lay Health Leader for Elders' Physical Fitness, Cognitive Function, Depression, and Quality of Life

Abstract: Purpose: This study was conducted to examine an exercise program using a lay health leader for elderly participants. The test covered physical fitness (grip strength, static balance and complex movement abilities), depression, cognitive function and quality of life. Methods: A quasi-experimental study using a non-equivalent control group pre-post design was employed. The participants were 62 elders from an institution for the aged, of whom 30 were included in the experimental group and 32 in the control group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
0
4
0
4
Order By: Relevance
“…As a result, the number of recipients of long-term care services surged, and the rate of those applying for the service rapidly increased from 0.5% in 2008 to 4.2% in 2011 4 ) . This has increased the number of long-term care facilities and more than doubled the number of elderly occupants 5 ) . Nonetheless, the quality of services provided by these nursing facilities has suffered from a lack of evidenced-based policies 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the number of recipients of long-term care services surged, and the rate of those applying for the service rapidly increased from 0.5% in 2008 to 4.2% in 2011 4 ) . This has increased the number of long-term care facilities and more than doubled the number of elderly occupants 5 ) . Nonetheless, the quality of services provided by these nursing facilities has suffered from a lack of evidenced-based policies 6 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In Jeong et al [ 24 ], an integrated therapy combining neurofeedback and cognicise for the elderly living alone in the community significantly improved their brain function and quality of life. In particular, depression in the elderly is a factor that influences quality of life, and Choi and Kim [ 40 ] reported that an exercise program significantly improved physical fitness, cognitive function, and quality of life, as well as depression in the elderly. Conversely, the results of this study are not in line with the results of previous studies verifying the effectiveness of single or combined interventions, including physical, cognitive, and neurofeedback exercises.…”
Section: Discussionmentioning
confidence: 99%
“…지금까지 연구되어진 치매예방 프로그램은 운동 프로그램 (Choi & Kim, 2013), 고령노인을 대상으로 인지강화 프로그램 (Sink et al, 2015), 경도인지장애를 가진 환자에게 인지중재 프로그램을 적용한 연구 (Rojas et al, 2013), 인지강화 프로그 램 (Han, Song, & Lim, 2010), 예술 프로그램 , 디지털 매체를 이용한 프로그램 (He, Park, Kang, & Jung, 2011), 통합치매예방 프로그램 (Son, Park, & Hwang, 2013) 등으로 지역사회 위주로 이루어지고 있다. 요양시설 입 소노인 중 경도치매나 중증치매 대상으로 율동적 동작을 이용 한 프로그램 (Lim, 2002), 동물로봇을 이용한 치매예방 프로그 램 (Lim et al, 2009) …”
Section: 요양시설노인의 치매예방 프로그램 참여 경험unclassified